2013
DOI: 10.1016/s1743-9191(13)60010-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety and effectiveness of image-guided percutaneous microwave ablation in cystic renal lesions Bosniak III or IV after 24 months follow up

Abstract: Purpose of the study: The aim of the study was to assess the efficacy, safety and effectiveness of percutaneous image-guided microwave ablation (MWA) in Bosniak category III or IV cystic renal lesions after 24 months follow-up duration. Methods: Between May 2008 and December 2012, computed tomography (CT)- or ultrasound (US)-guided MWA was performed in 6 patients with 7 cystic renal lesions (range 13.8-27 mm, mean 17.02 mm, SD 8.5 mm) Bosniak catgegory III or IV. The number of treatment sessions, treatment res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 24 publications
4
16
0
Order By: Relevance
“…Microwave ablation is a heat-based modality with a mechanism of cell death identical to that of other thermal ablation techniques, but which offers several physical advantages associated with the delivery of heat ( 5 6 ). As MWA has several advantages over RFA, including higher intratumoral temperatures, larger ablation volumes, and quicker ablation ( 7 ), multiple studies have recently investigated and reported the efficacy and safety of MWA ( 4 8 9 10 11 12 13 14 15 16 17 18 19 ). However, the results were varied, and most of the studies included a small number of patients, with limited precision of the estimated efficacy and safety of MWA.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave ablation is a heat-based modality with a mechanism of cell death identical to that of other thermal ablation techniques, but which offers several physical advantages associated with the delivery of heat ( 5 6 ). As MWA has several advantages over RFA, including higher intratumoral temperatures, larger ablation volumes, and quicker ablation ( 7 ), multiple studies have recently investigated and reported the efficacy and safety of MWA ( 4 8 9 10 11 12 13 14 15 16 17 18 19 ). However, the results were varied, and most of the studies included a small number of patients, with limited precision of the estimated efficacy and safety of MWA.…”
Section: Introductionmentioning
confidence: 99%
“…Even though Bosniak III and IV complex renal cysts are uncommon renal tumors, they are an important subgroup due to their risk of malignancy, which ranges from 16–100% and 90–100%, respectively ( 16 ). The current standard of care for both Bosniak III and IV lesions is surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In our sample, we treated small lesions (diameter: 1.5–4.1cm; mean: 2.5cm) and our results were not affected by this limitation. Interestingly, microwave ablation (MWA) may minimize thermal dispersion and reduce the “heat sink effect”, resulting in a positive outcome in larger cystic lesions, but only a single study to date has investigated the efficacy of MWA in only seven cystic renal lesions, which was not enough to adequately assess the efficacy of MWA ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bosniak III or IV cystic lesions may carry a particular risk for malignancy even if some of these lesions (particularly Bosniak III lesions) are proven to be benign after biopsy or surgery [35]. Park et al [36] proposed image-guided percutaneous RFA as a valuable alternative for cystic lesions unsuitable for surgery with excellent results.…”
Section: Percutaneous Mwa Of Renal Tumors: Clinical Seriesmentioning
confidence: 99%
“…Park et al [36] proposed image-guided percutaneous RFA as a valuable alternative for cystic lesions unsuitable for surgery with excellent results. Carrafiello et al [35] treated seven cystic renal lesions with a total applied energy of 45 W for an ablation time of 10 min and reported a technical success, defined as the correct positioning of the antenna into the lesion, of 100 %; a technical effectiveness, as the absence of thermo-ablative residues on CECT performed at 1 month after MWA treatment, of 100 %; and no major complications were recorded. This preliminary experience shows a potential role of US/CT-guided percutaneous MWA in treating Bosniak category III or IV cystic renal lesions, as a safe approach to treat selected patients unsuitable for surgery [35].…”
Section: Percutaneous Mwa Of Renal Tumors: Clinical Seriesmentioning
confidence: 99%